2013
DOI: 10.1159/000356524
|View full text |Cite
|
Sign up to set email alerts
|

Shunting in Acute Cerebral Venous Thrombosis: A Systematic Review

Abstract: Background and Purpose: The efficacy of cerebrospinal fluid shunting to reduce intracranial hypertension and prevent fatal brain herniation in acute cerebral venous thrombosis (CVT) is unknown. Method: From the International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT) and a systematic literature review, we retrieved acute CVT patients treated only with shunting (external ventricular drain, ventriculoperitoneal or ventriculojugular shunt). Outcome was classified at 6 months and final follow-up by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Studies were case reports, case series and a systematic review of cases. 122 The systematic review found only 15 CVT patients treated with shunting. These patients had a death rate of 22.2%, a death or dependency rate of 55.6% and a severe dependency rate 16.7%.…”
Section: (Recommendations)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were case reports, case series and a systematic review of cases. 122 The systematic review found only 15 CVT patients treated with shunting. These patients had a death rate of 22.2%, a death or dependency rate of 55.6% and a severe dependency rate 16.7%.…”
Section: (Recommendations)mentioning
confidence: 99%
“…Three patients with intracranial hypertension and no parenchymal lesions were treated with ventriculo-peritoneal shunt and regained independence. 122 In a recent case series of 14 CVT patients with acute hydrocephalus only one patient had a shunt. 121 Despite shunting the patient died.…”
Section: (Recommendations)mentioning
confidence: 99%
“…The authors conclude that some subgroups of patients (i.e., with increased ICP and without parenchymal lesions) could benefit from shunting. 3 Bithalamic infarction is usually caused by thrombotic events affecting the top of the basilar artery 4 but is also a known consequence of deep CVT. 4,6,20 The thalamic venous drainage is via the posterior thalamic veins that drain into the straight sinus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Clinical presentation is variable, and ranges from headaches with fever to seizures, focal neurological deficit, or coma. [1][2][3][4][5][6][7][8] The unspecificity of initial presentation often leads to a delayed diagnosis. When the deep cerebral venous system is occluded, venous hypertension can result in bithalamic infarction and edema.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation